Comparison of Outcomes of Haploidentical Peripheral Blood Stem Cell Transplantation Supported by Third-Party Cord Blood Versus Human Leukocyte Antigen-Matched Sibling Peripheral Blood Stem Cell Transplantation in Hematologic Malignancy Patients - Cheng, Tingting; Chen, Yan; Liu, Yi; Ma, Xia; Zeng, Cong; Chen, Xu; Wang, Shiyu; Xu, Yajing (Frontiers in Oncology, 2022)
Recent studies have shown that haploidentical hematopoietic stem-cell transplantation supported by third-party cord blood (haplo-cord-HSCT) results in rapid hematopoietic recovery, low incidences of graft-versus-host disease (GVHD) and relapse of hematologic malignancies. However, few reports have been published of haploidentical peripheral blood stem-cell transplantation supported by third-party cord blood (haplo-cord-PBSCT). To evaluate the outcomes of patients who underwent haplo-cord-PBSCT or HLA-matched sibling donor peripheral blood stem-cell transplantation (MSD-PBSCT), we retrospectively reviewed the clinical data of patients with hematologic malignancies that underwent haplo-cord-PBSCT (n = 93) or MSD-PBSCT (n = 72) in our hospital from March 2017 to December 2020. In the haplo-cord-PBSCT and MSD-PBSCT groups, the median time for neutrophil and platelet engraftment were 13 days vs. 12 days (P=0.07) and 16 days vs. 13 days (P=0.06), respectively. The 30-day cumulative incidences of neutrophil engraftment were 100.0% and 98.6% (P = 0.12), the 100-day cumulative incidences of platelet engraftment were 96.8% and 98.6% (P = 0.01), the 100-day cumulative incidences of grade II-IV and grade III-IV acute GVHD were 29.1% vs. 23.6% (P = 0.42) and 9.7% vs. 4.2% (P = 0.18), the cumulative incidences of total and moderate/severe chronic GVHD at 1 year were 26.5% vs. 17.4% and 8.1% vs. 4.5%, at 3 years were 34.7% vs. 34.3% (P = 0.60) and 13.6% vs. 10.6% (P = 0.49), correspondingly. The cumulative incidences of relapse at 1 year were 9.3% and 7.2%, at 3 years were 17.0% and 17.0% (P = 0.98), non-relapse mortality (NRM) at 1 year were 14.6% and 8.6%, at 3 years were 17.4% and 8.6% (P = 0.13) in two groups. And the probabilities of overall survival (OS), disease-free survival (DFS), GVHD-free/relapse-free survival (GRFS) at 1 year were 81.7% vs. 88.6%, 76.1% vs. 84.2%, 71.7% vs. 79.7%, at 3 years were 78.7% vs. 79.0%, 65.6% vs. 74.4%, 55.5% vs. 63.6% in corresponding group, P > 0.05. In conclusion, for patients with AML/MDS and ALL, haplo-cord-PBSCT results in similar outcomes compared with MSD-PBSCT and it may be a valid alternative transplantation method.